Comparison of Dentinal Defects Induced by Rotary, Reciprocating, and Hand Files in Oval Shaped Root Canal - An In-Vitro Study - Harakh Chand Branawal; Neelam Mittal; Prachi Rani; Aiyman Ayubi; Silviya Samad (Indian Journal of Dental Research)
Aim: To evaluate and compare the formation of dentinal defects using hand Hedstrom files, XP-Shaper, TruNatomy, and Reciproc Blue file systems when used for oval shaped root canals. Materials and Methods: One hundred and five extracted human mandibular premolars with single root and oval canals were selected for the study. Twenty-one teeth were unprepared (control), and the remaining teeth were divided into the prepared groups (n = 21), that is, Group H-Files, Group XP-Shaper, Group TruNatomy, and Group Reciproc Blue. All selected teeth were de-coronated perpendicular to the long axis of the tooth by using a diamond-coated disk with water cooling, leaving root segments approximately 16 mm in length. Each group was prepared according to the above file system. Then all roots were sectioned perpendicular to their long axes at 3, 6, and 9 mm from the apex using a diamond-coated disk under a continuous water stream. Each specimen was then checked for the presence of dentinal defects/microcracks. Result: The XP-Endo shaper group had the lowest number of defects (01/21 roots) 4.7%; TN (04/21) 19%, H-Files (04/21) 19%, and RC Blue (05/21) 23.8% had the highest incidence of defects. However, no significant difference was detected among these groups (P > 0.05). Conclusion: The motor-driven root canal instrumentation with rotary and reciprocating files and hand files may create microcracks in the radicular dentine, whereas the XP-Shaper file system produces minimal or less cracks compared to other tested rotary file systems and H-file instrumentation.